#### Answer

$-3-3i\sqrt3, -3+3i\sqrt3, \text{ and }6$

#### Work Step by Step

Use the Zero Factor Property by equating each factor to zero, then solve each equation:
\begin{array}{ccc}
&x-6=0 &\text{or} &x^2+6x+36=0
\\&x=6 & \text{or} &x^2+6x+36=0
\end{array}
Solve the second equation using the quadratic formula with $a=1, b=6, c=36$ to obtain:
$x=\dfrac{-6\pm \sqrt{6^2-4(1)(36)}}{2(1)}
\\x=\dfrac{-6\pm \sqrt{36-144}}{2}
\\x=\dfrac{-6\pm \sqrt{-108}}{2}
\\x=\dfrac{-6 \pm \sqrt{36(-3)}}{2}
\\x=\dfrac{-6 \pm 6\sqrt{-3}}{2}
\\x=\dfrac{-6\pm 6i\sqrt{3}}{2}
\\x=\dfrac{-6}{2}\pm \dfrac{6i\sqrt{3}}{2}
\\x=-3\pm3i\sqrt{3}$
Therefore, the solutions of the equation are:
$-3-3i\sqrt3, -3+3i\sqrt3, \text{ and }6$